Historic Building Information Modelling (HBIM) for Malaysian construction industry - Ali, Maisarah; Mohd Ismail, Kamsiah; Hashim, Khairusy Syakirin Has-Yun; Mohamad Suhaimi, Mohamad Saifulnizam; Mustafa, Muhammad Hadi (Malaysian Institute of Planners, 2018)
The Historic Building Information Modelling (HBIM) is widely accepted and practised all over the world. However, the adoption of HBIM within Malaysian construction industry is relatively low and slow because it demands new skill sets such as 3D modelling expertise, understanding of the approach, a lot of collaboration and it forces industry players to relate to each other differently. It is psychologically a very healthy environment, but not necessarily an easy transition. Since our cultural heritage buildings are limited, it is crucial for us to take care of it. Loss of information, insufficient documentation, poor maintenance, lack of technology adaptation, and reports reliability are among common problems the industry are facing. This paper review the attributes of HBIM based on literature, and its benefits, processes, tools, and challenges are highlighted. From this study, HBIM shows significant attributes that can contribute in providing a better understanding in handling historical buildings, besides allowing enhanced communication and documentation.